Effects of thrombolytic therapy on QT depression following acute myocardial infarction - Bhaktavatsalam, M.; Chavan, Manohar Shankarrao (International Journal of Advances in Medicine, 2018)
Background: Arrhythmias remains the major source of mortality from MI but with continuous ECG monitoring and the rapid availability of defibrillators, few with infarction die from ventricular fibrillation (VF) in hospitals. Perhaps for this reason or because of the lack of success in the prediction of VF, this problem has attracted relatively little recent attention. Objective of this study was to study effects of thrombolytic therapy on QT depression following acute myocardial infarction. Methods: Fifty patients of acute myocardial infarction (AMI) admitted to ICCU of a tertiary care hospital were studied for a period of three years. At the time of admission to ICCU a detailed history was taken in all patients. A general examination was done in all patients and vital signs of pulse, blood pressure, temperature was recorded. Results: VPC was the most common type of arrhythmia observed in the present study in 16% of the cases. Out of the 50 cases studied arrhythmias were found in only 23% of the cases. QTd as well as QTcd was more on admission among those who did not receive thrombolytic therapy. QT depression was significantly less in healthy individuals compared to patients with ventricular arrhythmias. Maximum i.e. four patients died due to ventricular arrhythmias or fibrillation. The mean value on admission was more in patients with ventricular arrhythmia compared to patients without ventricular arrhythmia. The mean value on admission as well as at discharge was more in patients with anterior. Conclusions: Present study to a large extent supports the contemporary hypothesis that higher QTc intervals and dispersions on the first day ECG of the patients with AMI caution us about the impending danger of VA and subsequent mortality.